'Pastoral practices' for quality improvement in a Kenyan clinical network. (December 2017) - McGivern, Gerry; Nzinga, Jacinta; English, Mike
Abstract: We explain social and organisational processes influencing health professionals in a Kenyan clinical network to implement a form of quality improvement (QI) into clinical practice, using the concept of 'pastoral practices'. Our qualitative empirical case study, conducted in 2015–16, shows the way practices constructing and linking local evidence-based guidelines and data collection processes provided a foundation for QI. Participation in these constructive practices gave network leaders pastoral status to then inscribe use of evidence and data into routine care, through championing, demonstrating, supporting and mentoring, with the support of a constellation of local champions. By arranging network meetings, in which the professional community discussed evidence, data, QI and professionalism, network leaders also facilitated the reconstruction of network members' collective professional identity. This consequently strengthened top-down and lateral accountability and inspection practices, disciplining evidence and audit-based QI in local hospitals. By explaining pastoral practices in this way and setting, we contribute to theory about governmentality in health care and extend Foucauldian analysis of QI, clinical networks and governance into low and middle income health care contexts. Highlights: Pastoral practices influence health professionals to implement quality improvement. Local evidence-based guidelines and audit processes provide a foundation for QI. A constellation of network leaders and local champions inscribed QI into practice. Discussion in network meetings facilitated reconstruction of professional identity. Professionals disciplined their own use of evidence and audit for QI purposes.